2015
DOI: 10.1021/jm501840b
|View full text |Cite
|
Sign up to set email alerts
|

Novel Small Molecule Inhibitors of Activated Thrombin Activatable Fibrinolysis Inhibitor (TAFIa) from Natural Product Anabaenopeptin

Abstract: Anabaenopeptins isolated from cyanobacteria were identified as inhibitors of carboxypeptidase TAFIa. Cocrystal structures of these macrocyclic natural product inhibitors in a modified porcine carboxypeptidase B revealed their binding mode and provided the basis for the rational design of small molecule inhibitors with a previously unknown central urea motif. Optimization based on these design concepts allowed for a rapid evaluation of the SAR and delivered potent small molecule inhibitors of TAFIa with a promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Anabaenopeptins are a highly diverse family of cyclic heptapeptides characterized by an ureidolinkage connecting the side chain amino acids to D-lysine. Members of this family are potent protease inhibitors and have served as lead products for the design of inhibitors against carboxypeptidase TAFIa (24). Although anabaenopeptin production has been principally demonstrated for N. punctiforme PCC 73102, no larger amount could be obtained for further characterization (18).…”
Section: Discussionmentioning
confidence: 99%
“…Anabaenopeptins are a highly diverse family of cyclic heptapeptides characterized by an ureidolinkage connecting the side chain amino acids to D-lysine. Members of this family are potent protease inhibitors and have served as lead products for the design of inhibitors against carboxypeptidase TAFIa (24). Although anabaenopeptin production has been principally demonstrated for N. punctiforme PCC 73102, no larger amount could be obtained for further characterization (18).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic for many anabaenopeptins is the inhibition of zinc-containing metalloexopeptidases such as carboxypeptidase A (CPA) and B (CPB) [ 14 , 25 ]. In experiments driven by pharmacological interests, anabaenopeptins have been shown to inhibit also carboxypeptidase U [ 26 ] and carboxypeptidase TAFIa, the thrombin activatable fibrinolysis inhibitor, important in the coagulation-fibrinolysis system [ 27 ]. Only a few studies so far have demonstrated activity of anabaenopeptins towards serine endopeptidases such as elastase, trypsin and chymotrypsin [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data collection was performed at the Swiss Light Source. Data processing and structure refinement was performed as described (25). The coordinates and structures factors of the crystal structure were submitted to the Protein Data Bank (code 5CGJ).…”
mentioning
confidence: 99%